PENGARUH VARIABEL MAKROEKONOMI DAN BEBERAPA SAHAM GLOBAL TERHADAP INDEKS HARGA SAHAM GABUNGAN 2015-2019 - Faizatul Mahmudah (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2021)
This study aims to explain the effect of the Dow Jones Industrial Average Index (DJIA). Kuala Lumpur Composite Index (KLSI), Shanghai Stock Composite Index (SSEC), inflation, interest rates, exchange rates,(Exchange rate), to the Composite Stock Price Index (IHSG). Using the Multiple Linear Regression analysis methods, with monthly samples from January 2015 to December 2019 which is resulted in 60 research samples. The test results using the Multiple Linear Regression method show that the DJIAI, KLCI has a positive and significant effect, the SSEC index and the BI rate have a negative and significant effect. Meanwhile, the inflation and exchange rate variables did not affect the IHSG movement. The implication of this research is to provide information to investors who must pay attention to several macroeconomic variables and several global stock indices if they want to invest in Indonesia.Keywords: Composite Stock Index, Macroeconomics, and Global Index.